THE EFFECTIVENESS OF THE SISKUEDES IN FINANCIAL MANAGEMENT IN JUNGWANGI VILLAGE - Sulistiya, Gita Nanda; Mursyidah, Lailul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to measure the effectiveness of the Village Financial System (SISKEUDES) in financial management within Jungwangi Village, Krian District. Method: A qualitative research design was employed, with data collected through field observations, interviews with key informants, and documentation analysis. Results: The findings, analyzed using the theoretical perspectives of Amas et al. (2020) and Aeni M. et al. (2022), indicate that the implementation of SISKEUDES in Jungwangi Village has been effective, as all stages of financial management have been carried out according to established procedures. However, challenges persist, particularly at the final reporting stage, where the central server often encounters errors or becomes inaccessible. This problem is attributed to high levels of simultaneous access by multiple village operators across different regions, creating system overloads. Novelty: This study contributes to the literature by highlighting not only the effectiveness of SISKEUDES in improving village-level financial governance but also by addressing technical barriers related to server capacity and system accessibility, which remain underexplored in previous research on digital financial management systems at the village level.